Efektivitas Pemungutan PPN PMSE di Indonesia: Analisis Dokumen Regulasi dan Arsip Fiskal - Nor Hasan; Adam Musthofa; Valin Arfina Sari Herlambang; Azarya Bartholomeus Djonien; Eva Dwi Fani (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the effectiveness of Value Added Tax collection on Electronic Commerce (VAT on PMSE) in Indonesia. The study employed a qualitative-descriptive approach with secondary data analysis, drawing on regulatory documents and fiscal archives from 2020 to 2026. The findings show that VAT on PMSE revenue grew consistently, reaching a cumulative total of IDR 38.76 trillion as of March 2026, contributing 76.7% of total digital economy tax revenue. However, its share of national VAT receipts remained limited at 0.82%. Regulatory dynamics reflect adaptive government responses, though fiscal inequality between foreign and domestic businesses remains a key challenge.